2015
DOI: 10.3109/00952990.2015.1059842
|View full text |Cite
|
Sign up to set email alerts
|

Rural substance use treatment centers in the United States: an assessment of treatment quality by location

Abstract: Background While previous research has added to the understanding of rural residents’ unique health challenges, much remains to be learned about the provision of substance use disorder (SUD) treatment in rural areas. A key question is difference in structural resources and quality of care between rural and urban treatment centers. Objective To examine differences in treatment quality in rural and urban centers and to determine if differences in treatment quality are contextualized by centers’ structural reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 33 publications
1
37
0
3
Order By: Relevance
“…This type of support can be critical for individuals returning to rural communities and small cities where social support and treatment services are less available (Applegate & Sitren, ; Weisheit & Wells, ; Zajac et al., ). Researchers have suggested, however, that high staff turnover and fewer qualified staff can challenge the efficacy of supervision in rural areas (Edmond et al., ; Hipp et al., ; Logan et al., ), which perhaps exacerbates our finding about ad hoc enforcement. Although beyond the scope of the current work, there is a potential opportunity to train correctional staff on the unique needs of individuals under correctional supervision in smaller towns and rural areas as most correctional practices are developed for metropolitan populations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This type of support can be critical for individuals returning to rural communities and small cities where social support and treatment services are less available (Applegate & Sitren, ; Weisheit & Wells, ; Zajac et al., ). Researchers have suggested, however, that high staff turnover and fewer qualified staff can challenge the efficacy of supervision in rural areas (Edmond et al., ; Hipp et al., ; Logan et al., ), which perhaps exacerbates our finding about ad hoc enforcement. Although beyond the scope of the current work, there is a potential opportunity to train correctional staff on the unique needs of individuals under correctional supervision in smaller towns and rural areas as most correctional practices are developed for metropolitan populations.…”
Section: Discussionmentioning
confidence: 91%
“…Rural communities have fewer amenities and services including access to treatment programs, subsidized housing, and food support when compared with urban communities (Logan et al., ; Wodahl, ). Justice systems in rural locales rely on a smaller tax base, and community supervision officers have fewer and more distant resources for clients (Applegate & Sitren, ; Weisheit & Wells, ; Zajac, Hutchison, & Meyer, ), which is compounded by high employee turnover and fewer qualified staff (Edmond, Aletraris, & Roman, ; Hipp, Janetta, Shah, & Turner, ; Logan et al., ). Stable, affordable housing is also less prevalent in rural areas (Wodahl, ), and residents rarely have access to halfway houses, homeless shelters, and other types of transitional facilities that are more common in urban communities (Jackson & Shannon, ).…”
Section: Reentry and Placementioning
confidence: 99%
“…Most of the research on access to treatment has focused on individual characteristics such as attitudinal barriers and perceived need, as well as financial barriers (Andrade, Alonso, Mneimneh, et al, ; Sareen et al, ); those that focus on geographical barriers have found location is not often cited as a barrier to treatment by individuals (Alegria, Bijl, Lin, Walters, & Kessler, ). From a geographic perspective, however, research has devoted attention to the lack of providers in rural areas (Davis et al, ; Edmond, Aletraris, & Roman, ; Ringel & Sturm, ; Skubby, Bonfine, Novisky, Munetz, & Ritter, ), rather than the locations of treatment providers in urban environments. To date, there have been no examinations of social processes or environmental features of streets that house calls to the police for mental health crises, and specifically whether having a service provider nearby prevents crisis calls to the police.…”
Section: Mental Healthmentioning
confidence: 99%
“…Other studies have reported major geographic disparities in the number of physicians treating OUD in rural versus urban areas (Sigmon, 2014; Jones et al, 2015), potentially related to the fact that clinics specializing in opioid maintenance agonist therapy are often sparse in rural areas and may not offer a full range of treatment options compared to urban areas (Sigmon, 2014; Edmond et al, 2015). Finally, OUD severity was hypothesized to play a role in treatment preference since those with more severe OUD are likely to know others that have tried various treatment options and might have developed stronger preferences for certain treatments (specifically MATs) (Rounsaville and Kleber, 1985).…”
Section: Discussionmentioning
confidence: 99%